MAKNA SUKSES DALAM IKLAN ROKOK LA LIGHTS - Februnia Mura Ngguna; Fathul Qorib (Universitas Tribhuwana Tunggadewi, 2019)
Abstract: This study aims to find out the meaning of success contained in LA Lights cigarette commercials